Generic frame model for simulation of earthquake responses of steel moment frames. - Nakashima, Masayoshi (Earthquake engineering & structural dynamics.)
This paper presents a generic frame (GF) model useful for the simulation of earthquake responses of steel moment frames. Adopting the assumption that all rotations at joints lying at each floor level are identical, the model requires the solution of significantly fewer degrees of freedom than models with member by member representation. Procedures to construct a GF model that represents a multi storey, multi span frame are detailed. The model can allow for panel zone behaviour as well. The accuracy of the GF model in predicting maximum storey drifts and member plastic rotations is calibrated for two example frames against a variety of ground motions. Errors associated with the model are found to be negligible in light of the variability of responses attached to randomness and uncertainties of earthquake ground motions. The GF model is effective in conducting extensive numerical analyses needed for the identification and characterization of primary structural parameters that control the earthquake responses of steel moment frames, thereby contributing to further advancement of performance based design.